Developing a national snapshot of pesticide use practices in childcare centers using three different communication venues. Issue 3 (3rd July 2018) - Anderson, Marcia
ABSTRACT: Children spend as much as ten hours per day, five days a week in childcare centers and preschools. In providing healthy environments, these facilities deal with a variety of pest and pesticide issues influenced by their geographic location, local environment, and pesticide regulations. Some rely extensively on pesticides while others use integrated practices to address pest problems. Reducing the unnecessary exposure of children to pests and pesticides can be an important public health measure. Surveys, webinars, and an outreach project were used to demonstrate the dependence of childcare centers on pesticides. Webinars and on-site visits were effective in inform child care administrators and staff about an integrated approach to pest management that reduces the unnecessary exposure of children to pests and pesticides.